Rehabilitation procedure in patients with stable angina pectoris after percutaneous angioplasty of the coronary arteries - Kocik, Bożena; Spannbauer, Anna; Mika, Piotr (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2018)
Percutaneous coronary angioplasty (PCI) is a technique of invasive treatment of coronary artery disease by expanding and restoring normal circulation in the narrowed coronary artery, caused by the ongoing disease process. The most common reason for coronary artery disease, called stable angina pectoris due to clinical symptoms, is coronary atherosclerosis. The treatment of patients with stable angina pectoris after percutaneous coronary angioplasty is based primarily on the guidelines of the European Society of Cardiology. The key message of the authors is the important role associated with the strategy of cardiovascular disease prevention in order to modify risk factors, and the introduction of permanent lifestyle changes based, among other things, on increased physical activity. The combination of knowledge and skills of caregivers such as doctors, nurses, nutrition experts, and experts in cardiological rehabilitation and conscious participation of the patient in the treatment process is a guarantee of therapeutic success.